Produção de proteases colagenolíticas de Aspergillus heteromorphus URM 0269 e extração em sistemas de duas fases aquosas para aplicação na hidrólise de colágeno - COSTA, Beatriz de Aquino Marques da (2022)
The increase in consumer demand for products that contain functional ingredients that are beneficial to their health and well-being has increased the market for agents of this nature, such as collagen and its hydrolysates. Thus, research for alternatives that make one or more stages of the production of these compounds more cost-effective is constantly encouraged, leading to the investigation of the use of filamentous fungi to produce proteases, simpler means of extraction and purification of these enzymes and the potential of fish residues as sources of collagen. In this context, the objective of the present work was to produce collagenolytic proteases from Aspergillus heteromorphus URM 0269 using solid-state fermentation, extract them using aqueous two-phase system (ATPS) and apply them in collagen hydrolysis. For this, the microorganism was cultivated (3g of wheat bran, 20% humidity, 30°C, 96) to obtain the crude enzymatic extract. The crude extract was then submitted to a factorial design (23) for the purification of collagenolytic proteases using ATPS, having as independent variables: PEG molar mass (MPEG), PEG concentration (CPEG) and sulfate (Csulf). Subsequently, the proteases extracted by PEG/sulfate ATPS were evaluated for their stability at different pH levels (4.0 – 11.0). To obtain the collagen, residues of red snapper (Lutjanus analis) skin were submitted to treatment with acetic acid (0.5M). The enzyme was partitioned preferentially to the PEG-rich phase (K>1) whose highest purification and recovery factor (PF = 6.256 and Y= 404.432%) was obtained using MPEG 8000 g/mol, CPEG 30%, Csulf 10%. The evaluation of the effect of pH on the enzymatic activity revealed that the extraction in ATPS was able to increase the pH range with high enzymatic activity (7.0 – 11.0) compared to that observed in the crude extract (6.0 – 7.0), as well as its stability, maintaining at least 80% of their protease activity after 20 hours of incubation for all pH levels analyzed, except for pH 11.0. The extraction of collagen from red snapper skin resulted in a yield of 8.056% and the hydrolysis assay using the enzymatic samples of crude extract and those of the PEG phase of the ATPS were able to hydrolyze the extracted collagen, both obtaining a peak of hydrolysis after 36 hours of treatment. From the results obtained in the present work, it is expected that more studies will be developed to elucidate the properties and biological potential of the hydrolysates produced.